The complete chloroplast genome assembly of Amorphophallus kiusianus makino 1913 (araceae) from Southern China - Yong Gao; Si Yin (Mitochondrial DNA. Part B. Resources, 2024)
AbstractThe mountainous region of southern China has been characterized by its complicated environment and topography. Amorphophallus kiusianus Makino 1913 is a representative species of extreme habitat preference that resides mainly in this region. To help study the genetic differentiation mechanisms of A. kiusianus populations, we sequenced the first chloroplast genome of this species using next-generation sequencing. The chloroplast genome was 166,269 bp in length with an average GC content of 36% (GenBank accession number: PP072243). The lengths of the large single-copy region (LSC), small single-copy region (SSC), and two inverted repeats (IRs) were 90,701 bp, 14,802 bp, 31,383 bp, and 31,383 bp, respectively. One hundred and twenty-nine genes were annotated in the chloroplast genome, including 84 protein-coding genes, 8 rRNA genes, and 37 tRNA genes. The phylogenetic tree suggested a close relationship among A. kiusianus, A. yunnanensis, and A. coaetaneus. The chloroplast genome reported in this study provides valuable genomic resources for the future phylogeographic research of A. kiusianus.